Permafrost degradation as a control on hydrogeological regime shifts in a warming climate - Bense, V.F.; Kooi, H.; Ferguson, G.; Read, T. (Journal of Geophysical Research: Earth Surface, 2012)
Using numerical models, we evaluate hydrogeological regime changes in high-latitude river basins under conditions of ground surface warming. These models describe transient heat- and fluid flow coupled to the hydrogeological impacts of phase-changes from ice to liquid water. We consider an idealized unconsolidated sedimentary aquifer system in which groundwater flow is driven by topography, representing a series of small drainage basins in riverine terrain of relatively subdued topography. Various temporal and spatial surface temperature conditions are considered to control the initial permafrost distributions for the simulations. The simulated rates of increase in groundwater contribution to streamflow during and after permafrost thaw, are in the order of magnitude comparable to hydrogeological regime changes over the past decades as reported for several (sub-)Arctic rivers. The simulations further show that two distinct features of the subsurface response control the temporal evolution of base flow increase: (1) shifts in aquifer permeability architecture during permafrost degradation and (2) uptake of water into aquifer storage when sub-permafrost hydraulic heads rise. Model analysis shows that the latter process delays base flow increase by several decades to centuries. In order to evaluate the relative importance of both processes in natural systems, the current hydraulic regime of sub-permafrost aquifer systems as well as patterns of permafrost heterogeneity, taliks and their hydraulic connectivity are insufficiently known. © 2012. American Geophysical Union. All Rights Reserved.